Are tattoos associated with employment and wage discrimination? Analyzing the relationships between body art and labor market outcomes. (May 2019) - French, Michael T; Mortensen, Karoline; Timming, Andrew R
Do job applicants and employees with tattoos suffer a penalty in the labor market because of their body art? Previous research has found that tattooed people are widely perceived by hiring managers to be less employable than people without tattoos. This is especially the case for those who have visible tattoos (particularly offensive ones) that are difficult to conceal. Given this backdrop, our research surprisingly found no empirical evidence of employment, wage or earnings discrimination against people with various types of tattoos. In our sample, and considering a variety of alternative estimation techniques, not only are the wages and annual earnings of tattooed employees in the United States statistically indistinguishable from the wages and annual earnings of employees without tattoos, but tattooed individuals are also just as likely, and in some instances even more likely, to gain employment. These results suggest that, contrary to popular opinion as well as research findings with hiring managers and customers, having a tattoo does not appear to be associated with disadvantage or discrimination in the labor market.